Plasmodium falciparum AMA1 and CSP antigen diversity in parasite isolates from southern Ghana - Kusi, Kwadwo A.; Amoah, Linda E.; Acquah, Festus Kojo; Ennuson, Nana Aba; Frempong, Abena F.; Ofori, Ebenezer A.; Akyea-Mensah, Kwadwo; Kyei-Baafour, Eric; Osei, Frank; Frimpong, Augustina; Singh, Susheel K.; Theisen, Michael; et al. (Frontiers in Cellular and Infection Microbiology, 2024)
Introduction Diversity in malarial antigens is an immune evasion mechanism that gives malaria parasites an edge over the host. Immune responses against one variant of a polymorphic antigen are usually not fully effective against other variants due to altered epitopes. This study aimed to evaluate diversity in the Plasmodium falciparum antigens apical membrane antigen 1 (PfAMA1) and circumsporozoite protein (PfCSP) from circulating parasites in a malaria-endemic community in southern Ghana and to determine the effects of polymorphisms on antibody response specificity. Methods The study involved 300 subjects, whose P. falciparum infection status was determined by microscopy and PCR. Diversity within the two antigens was evaluated by msp2 gene typing and molecular gene sequencing, while the host plasma levels of antibodies against PfAMA1, PfCSP, and two synthetic 24mer peptides from the conserved central repeat region of PfCSP, were measured by ELISA. Results Of the 300 subjects, 171 (57%) had P. falciparum infection, with 165 of the 171 (96.5%) being positive for either or both of the msp2 allelic families. Gene sequencing of DNA from 55 clonally infected samples identified a total of 56 non-synonymous single nucleotide polymorphisms (SNPs) for the Pfama1 gene and these resulted in 44 polymorphic positions, including two novel positions (363 and 365). Sequencing of the Pfcsp gene from 69 clonal DNA samples identified 50 non-synonymous SNPs that resulted in 42 polymorphic positions, with half (21) of these polymorphic positions being novel. Of the measured antibodies, only anti-PfCSP antibodies varied considerably between PCR parasite-positive and parasite-negative persons. Discussion These data confirm the presence of a considerable amount of unique, previously unreported amino acid changes, especially within PfCSP. Drivers for this diversity in the Pfcsp gene do not immediately seem apparent, as immune pressure will be expected to drive a similar level of diversity in the Pfama1 gene.